HOF•CH3CN—The Most Potent Oxygen Transfer Agent for a Large Variety of Organic Molecules - Shlomo Rozen (Molecules)
The complex of hypofluorous acid with acetonitrile—HOF•CH3CN—is the only substance possessing a truly electrophilic oxygen. This fact makes it the only tool suitable for transferring oxygen atoms to sites that are not accessible to this vital element. We will review here most of the known organic reactions with this complex, which is easily made by bubbling dilute fluorine through aqueous acetonitrile. The reactions of HOF•CH3CN with double bonds produce epoxides in a matter of minutes at room temperature, even when the olefin is electron-depleted and cannot be epoxidized by any other means. The electrophilic oxygen can also substitute deactivated tertiary C-H bonds via electrophilic substitution, proceeding with full retention of configuration. Using this complex enables transferring oxygen atoms to a carbonyl and oxidizing alcohols and ethers to ketones. The latter could be oxidized to esters via the Baeyer–Villiger reaction, proving once again the validity of the original Baeyer mechanism. Azines are usually avoided as protecting groups for carbonyl since their removal is problematic. HOF•CH3CN solves this problem, as it is very effective in recreating carbonyls from the respective azines. A bonus of the last reaction is the ability to replace the common 16O isotope of the carbonyl with the heavier 17O or 18O in the simplest and cheapest possible way. The reagent can transfer oxygen to most nitrogen-containing molecules. Thus, it turns practically any azide or amine into nitro compounds, including amino acids. This helps to produce novel α-alkylamino acids. It also attaches oxygen atoms to most tertiary nitrogen atoms, including certain aromatic ones, which could not be obtained before. HOF•CH3CN was also used to make five-member cyclic poly-NO derivatives, many of them intended to be highly energetic materials. The nucleophilic sulfur atom also reacts very smoothly with the reagent in a wide range of compounds to form sulfone derivatives. While common sulfides are easily converted to sulfones by many orthodox reagents, electron-depleted ones, such as Rf-S-Ar, can be oxidized to Rf-SO2-Ar only with this reagent. The mild reaction conditions also make it possible to synthesize a whole range of novel episulfones and offer, as a bonus, a very easy way to make SxO2, x being any isotope variation of oxygen. These mild conditions also helped to oxidize thiophene to thiophen-S,S-dioxide without the Diels–Alder dimerizations, which usually follow such dioxide formation. The latter reaction was a prelude to a series of preparations of [all]-S,S-dioxo-oligothiophenes, which are important for the efficient preparation of active layers in field-effect transistors (FETs), as such oligomers are considered to be important for organic semiconductors for light-emitting diodes (LEDs). Several types of these oligothiophenes were prepared, including partly or fully oxygenated ones, star-oligothiophenes, and fused ones. Several [all]-S,S-dioxo-oligo-thienylenevinylenes were also successfully prepared despite the fact that they also possess carbon–carbon p centers in their molecules. All oxygenated derivatives have been prepared for the first time and have lower HOMO-LUMO gaps compared to their parent compounds. HOF•CH3CN was also used to oxidize the surface of the nanoparticles of oligothiophenes, leaving the core of the nanoparticle unchanged. Several highly interesting features have been detected, including their ability to photostimulate the retinal neurons, especially the inner retinal ones. HOF•CH3CN was also used on elements other than carbon, such as selenium and phosphor. Various selenides were oxidized to the respective selenodioxide derivatives (not a trivial task), while various phosphines were converted efficiently to the corresponding phosphine oxides.